Pemanfaatan Limbah Batang Pisang sebagai Pakan Alternatif pada Penggemukkan Ternak Sapi - Yan Alpius Loliwu; James Marota Taralalu (Mosintuwu Jurnal Pengabdian Kepada Masyarakat, 2021)
Banana stems are agricultural waste that can be processed into quality animal feed raw materials that can be utilized by farming communities and help in anticipating forage shortages in the dry season. This service activity aims to transfer knowledge and technology in the field of animal husbandry to the farmer-breeding community so that it can be adopted and applied in the business of fattening cattle. Method of Implementation of Community Service activities carried out in synergy between Universities and Partner Groups in the form of socialization, delivery of theory and practice. The results of the implementation of Community Service activities showed a positive response from the partner group as indicated by the presence of the management and the number of group members reached 80% (8 out of 10 people). The results of the discussion on service activities regarding the utilization of banana stem agricultural waste as raw material for animal feed have been known in principle, but the farming community does not yet know the processing method used to improve its quality. The results of the practice of processing banana stem waste show a very satisfactory success rate because it is well processed which is indicated by the distinctive aroma and taste, as well as the very high palatability of livestock. The conclusion is that the seriousness of active and interactive participation of partner groups in community service activities can make a positive contribution in adopting science and technology and can improve the quality and quantity of animal feed that can be used to anticipate feed shortages in cattle fattening efforts.